Comunidade que Sustenta a Agricultura (CSA): experiência impulsionada pela economia solidária para a sociedade do bem viver - Romeiro, Jéssica Bittencourt (2024)
This study discusses the Community of Supported Agriculture (CSA). The organization of this production and consumption network takes place in a participatory system where the community finances agroecological production, establishing bonds of trust between farmers and consumers. With the objectives of valuing rural production, responsible and conscious consumption, cooperation and self-management, characteristics that are present in the practice of the Solidarity Economy for the construction of a Good Living society. Based on the CSA experience, which emerged at the Solidarity Economy Fair, located in the central region of Rio Grande do Sul, we sought to understand the relationships established between producers and consumers, explore the subjects' perception of CSA, investigate consumption customs and identify challenges and potential. We sought to understand the phenomenon from the subjects' perception, in accordance with Weber's comprehensive sociology. As a methodological procedure, the research is classified as a qualitative, exploratory and descriptive approach, being developed through action research. Semi-structured interviews were carried out, with a script seeking to address the objectives of this study. The CSA emerging from the Solidarity Economy proved to be relevant for the construction of the analyzed group, which leads to the Good Living society. Participation in a CSA impacts changing food production and consumption customs. The values that motivated the construction of this CSA were the search for safe and quality food with a direct relationship with those who produce and the appreciation of family farming. For farmers, the guarantee of monthly financing is the main motivating factor, in addition to the appreciation of family farming and local development. As challenges, based on experience, those interviewed point to the lack of dissemination of this production and consumption model, the diversification of food production due to extreme weather conditions and, for some consumers, distribution logistics. The potential was identified as expanding the movement, the high commitment and cooperation of the participants, the sustainability of the system and shortening the distance between people and food. There is a consumer profile that makes this CSA model inaccessible to people in socially vulnerable situations. The study had limitations arising from the pandemic scenario faced during the research. The small sample group did not allow for statistical analyzes of greater effect. CSA is characterized as a model that moves towards a Good Living society, with collective concerns and connections to the land, valuing family farming practices, inserted in a space of Solidarity Economy